(untitled) (Revista de Administração, 2016)
This study investigates the influence of ownership concentration on earnings quality of Brazilian firms. This topic is relevant considering the substantially low number of companies with diffuse ownership structure in Brazil in comparison to US, where most studies about earnings quality have been performed. The Brazilian setting permits us to complement Givoly, Hayn, and Katz (2010) analysis between the potential explanations for the relation between ownership structure and earnings quality based on both the "demand" and "opportunistic behavior" hypothesis. To examine this relationship, we employ two measures as proxies of earnings quality: earnings persistence and asymmetric timeliness (conservatism). Our results are consistent with the "demand" hypothesis and indicate that earnings represent a more consistent indicator of future performance when ownership structure becomes more dispersed. Our results contribute to the literature because it suggests that the quality of accounting numbers have to be assessed considering aspects related to ownership concentration (even when analyzing earnings from public firms). It also contributes to the investment community because it shows that earnings forecast accuracy may be influenced by ownership structure.